Kontribusi Media Pembelajaran Dan Gaya Belajar Dalam Meningkatkan Perolehan Belajar: The Contribution of Learning Media and Learning Styles to Enhancing Learning Achievement - Mundir Mundir (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2003)
Low student learning outcomes in Research Methodology courses are often attributed to poorly designed textbooks and insufficient attention to individual learning styles. This study is grounded in instructional communication and Gagne’s learning conditions theory, which emphasize the roles of instructional media and learner characteristics in shaping academic achievement. The research examined the effects of instructional media and learning styles on students’ learning gains. A 2x2 factorial design with pre- and post-test control groups was employed, involving 40 students selected through quota random sampling from STAI Ibrahimy. The test’s reliability coefficient was 0.731, and data were analyzed using two-way ANOVA. The findings revealed that instructional media significantly contributed to learning outcomes, with the experimental group using structured teaching materials outperforming the control group using conventional textbooks. However, no significant differences in learning outcomes were found based on visual or auditory learning styles, nor was there a significant interaction effect between instructional media and learning styles. The study concludes that well-designed instructional media can substantially enhance learning achievement regardless of students’ dominant learning styles. It is recommended that higher education institutions develop comprehensive, self-instructional teaching materials for methodology courses, while further research should explore other moderating factors such as motivation or prior knowledge. Rendahnya hasil belajar mahasiswa pada mata kuliah Metode Penelitian sering disebabkan oleh buku teks yang tidak dirancang secara sistematis serta kurangnya perhatian terhadap gaya belajar individu. Penelitian ini berpijak pada teori komunikasi pembelajaran dan kondisi belajar Gagne, yang menekankan peran media pembelajaran dan karakteristik pebelajar dalam pencapaian akademik. Tujuan penelitian adalah menguji kontribusi media pembelajaran dan gaya belajar terhadap perolehan belajar mahasiswa. Metode eksperimen dengan desain faktorial 2x2 dan pre-test post-test control group digunakan, melibatkan 40 mahasiswa STAI Ibrahimy melalui quota random sampling. Koefisien reliabilitas tes sebesar 0,731, dan analisis data menggunakan ANOVA dua jalur. Hasil penelitian menunjukkan bahwa media pembelajaran berkontribusi signifikan terhadap perolehan belajar, di mana kelompok yang menggunakan bahan ajar terstruktur memperoleh hasil lebih tinggi dibandingkan kelompok dengan buku teks konvensional. Namun, tidak ditemukan perbedaan signifikan dalam perolehan belajar berdasarkan gaya belajar visual maupun auditorial, serta tidak ada efek interaksi antara media pembelajaran dan gaya belajar. Kesimpulannya, media pembelajaran yang dirancang dengan baik mampu meningkatkan hasil belajar secara substansial terlepas dari gaya belajar mahasiswa. Rekomendasi penelitian ini adalah agar perguruan tinggi mengembangkan bahan ajar lengkap untuk mata kuliah metode penelitian, serta perlunya kajian lebih lanjut terhadap faktor moderator lain seperti motivasi atau kemampuan awal.